SAT0215 Liver blood test abnormalities are rare in patients on methotrexate: evidence from a large cohort of inflammatory arthritis patients. (12th June 2018) - Malley, T.; Corfield, G.; Heneghan, D.; Kitchen, J.
Abstract : Background: National British Society of Rheumatology guidelines for monitoring non-biologic disease-modifying anti-rheumatic drugs (DMARDs) suggest reducing the frequency of blood monitoring for patients on stable doses of methotrexate to 12 week intervals. 1 Implementation of this recommendation would reduce pressure on services, reduce costs and enhance patient experience. However, it remains unclear whether patient safety would be compromised with 12 week interval blood monitoring in a real world setting. Objectives: The primary objective was to establish whether reducing blood monitoring frequency from monthly to 12 week intervals would compromise the safety of patients on methotrexate by either late detection or missing signs of transaminitis on blood results. Methods: Between June 2016 and July 2017, monthly liver function test results were monitored in 1, 964 patients on methotrexate. Demographic data were collected and abnormal results were reviewed. Patients with raised alanine aminotransferase (ALT) (>34 U/l) were categorised as either: isolated (only one abnormal result), persistent (at least two consecutive abnormal results) or intermittent (more than one abnormal result separated by at least one normal result). For those with an ALT>100 U/l, medical records were reviewed to determine causality. Results: ALT results for 1, 964 patients were reviewed (F=1288, M=676). 775 were on one concomitant DMARD, 82 were on triple DMARD therapy (hydroxychloroquine and sulfasalazine) and 396 were on biologic therapy. Indications for methotrexate were rheumatoid arthritis (n=1262), psoriatic arthritis (n=611) and spondyloarthropathy (n=91). Ten patients (0.51%) had an ALT>100 U/l over 13 months: 8 were persistent, 1 was intermittent and 1 was isolated. Further investigations revealed fatty liver in one patient (necessitating methotrexate discontinuation) and a weakly positive anti-smooth muscle antibody in another (both with persistent ALT>100), but were unremarkable in the other 8. A further 48 patients had at least one ALT rise of 35–100 U/l which did not alter therapy. Conclusions: Over 13 months monitoring 1, 964 patients on methotrexate, only 0.51% developed an ALT>100 U/l of whom only one patient discontinued methotrexate. In this patient the ALT rise was persistent for more than 12 weeks. Therefore 12 week interval blood monitoring would have reliably detected this abnormality. In those with intermittent and isolated ALT rises >100 U/l, there were no concerning features requiring cessation of methotrexate. This suggests that although a proportion of ALT rises would not be captured on 12 week blood monitoring intervals, isolated or intermittent rises are unlikely to pose harm to patients. Reducing the frequency of blood monitoring to 12 week intervals would be an efficient use of resources whilst being safe for patients. Furthermore this study provides evidence that less frequent blood monitoring may be feasible in patients on combination DMARDs, particularly relevant in an era where combination treatment is the standard of care in inflammatory arthritis. Reference: [1]Ledingham J, et al. BSR and BHPR guideline for the prescription and monitoring of non-biologic disease-modifying anti-rheumatic drugs. Rheumatology2017;56:865–868. Disclosure of Interest: None declared